HUKUM PERLINDUNGAN ANAK AKIBAT PERCERAIAN DALAM KELUARGA: STUDI PERBANDINGAN KITAB UNDANG-UNDANG PERDATA DAN KOMPILASI HUKUM ISLAM - Aiz, Muhammad; 1, Muzdalifah (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2013)
The problem of Oils study is how the child protection law of divorce in the family according to Law No. 23 of2002, on Child Protection and the Islamic Law concerning post-divorce child custody and where the location of the similarities and differences of these two legal instruments in the present context? Research using the normative approach by conducting a review of the child in the custody of the Child Protection Law and Islamic law with reference to the texts of the Qur'an and al-Hadlth. As well as legislation related to child issues, after the necessary data collected is then analyzed descriptively presented and described in a systematic, factual and accurate. Once known child custody In the Child Protection Act then compared with Islamic law to get a conclusion. The results of the study of which is, in the Child Protection Act parents have equal rights and equal to nurture and care for children while the children in the custody of Islamic law are explicitly given to the mother after the divorce